System-Social Strategy for Trust Building in Mobile Banking Context - Phyo Min Tun; Cherisa Nantha; Srivallop, Atikom; Siripongdee, Surapong (Thailand and The World Economy, 2024)
This paper aims to examine the roles of system and social perspectives for trust building in the mobile banking context and the moderating effects of demographic groups on direct effects on trust. The study investigates system perspectives (system quality and system usefulness), social perspectives (social influence and word-of-mouth), and moderators (gender, age, and education) as an exploratory study. This study employed deductive reasoning quantitative research approach by using 294 datasets. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to calculate the factors' validity and reliability. The Structural Equation Modeling (SEM) technique was employed to estimate direct effects, indirect effects, and moderator effects. The findings reveal that system quality, system usefulness, and word-of-mouth affect trust, while social influence has an insignificant effect on trust. Besides, system quality has a significant effect on system usefulness, and social influence has a significant effect on word-of-mouth, respectively. Also, education level is significantly moderating the direct effect of word-of-mouth and trust. This research extends the understanding of the system and social perspectives that influence trust and might be a barrier to mobile banking adoption in Myanmar. Also, the findings of this research will assist private banks in recognizing the behavior patterns of customers so that they can create a proper system-social strategy to boost the confidence of customers about mobile banking and fulfill the knowledge gap regarding system and social aspects.